Transportation of whey protein-derived peptides using Caco-2 cell model and identification of novel cholesterol-lowering peptides - Liu , Feifan; Liu , Mingzhen; Zhang , Tao; Zhao , Xuan; Wang , Xiaozhi; Kong , Weimei; Cui , Li; Luo , Haibo; Guo , Lili; Guo , Yuxing (Food & Nutrition Research, 2023)
Background: The increasing morbidity and mortality of cardiovascular disease have become a major factor in human death. Serum cholesterol is considered to be an important risk factor for inducing coronary heart disease, atherosclerosis and other cardiovascular diseases. To screen intestinal absorbable functional small peptides with cholesterol-lowering activity by enzymatic hydrolysis of whey protein and develop cholesterol-based functional food that may become a substitute for chemically synthesized drugs, providing new ideas for diseases caused by high cholesterol.Objective: This study aimed to evaluate the cholesterol-lowering activity of intestinal absorbable whey protein-derived peptides hydrolyzed by alkaline protease, trypsin and chymotrypsin, respectively.Method: The whey protein hydrolysates acquired by enzymatic hydrolysis under optimal conditions were purified by a hollow fiber ultrafiltration membrane with a molecular weight cutoff of 10 kDa. The fractions obtained by Sephadex G-10 gel filtration chromatography were transported through a Caco-2 cell monolayer. The transported peptides were detected in the basolateral aspect of Caco-2 cell monolayers using ultra- performance liquid chromatography-tandem mass spectrometry (UPLC-MS).Results: His-Thr-Ser-Gly-Tyr (HTSGY), Ala-Val-Phe-Lys (AVFK) and Ala-Leu-Pro-Met (ALPM) were unreported peptides with cholesterol-lowering activity. The cholesterol-lowering activities of the three peptides did not change significantly during simulated gastrointestinal digestion.Conclusion: This study not only provides theoretical support for the development of bioactive peptides that can be directly absorbed by the human body, but also provides new treatment ideas for hypercholesterolemia.